Analisis Peluang Riset Pendidikan Sains Terkait Media Pembelajaran: A Systematic Literature Network Analysis - Rahmi Zulva; Agus Setiawan; Andi Suhandi (Postgraduate, University of Mataram, 2023)
The aim of this study is to describe the trend data of research related to learning media. The research method used is the Systematic Literature Network Analysis (SLNA) method. The data for this study consists of research articles on learning media without any time limitations. Articles were collected from the Scopus database, which includes IEEE, Springer, and the search application Publish or Perish (PoP). In the search engine, articles on learning media were first found in 2002, and a total of 1708 articles were retrieved. After filtering by title, 120 articles were obtained, and based on the keywords from these articles, 80 eligible articles were identified for analysis. The analysis results show that the number of studies and research citations fluctuate. Topics frequently discussed in the context of learning media include skills, approaches, and the latest on interactive multimedia. For further research directions, it can be associated with the use of interactive multimedia in explaining science learning that uses a phenomenon-based learning model. This is because science learning can explain phenomena that occur in everyday life